ANOVA studies and control factors effect analysis of cobalt based microwave clad. (2021) - Vishwanatha, J.S.; Hebbale, Ajit M.; Kumar, Nithin; Srinath, M.S.; Badiger, Ravindra I.
Abstract: In today's world slurry handling equipments are facing lot of engineering problems which is namely erosion. Slurry erosion plays a very important role in the design and operation of slurry transportation systems. In the work an attempt is made to reduce slurry erosion by cobalt based clad developed through microwave energy. The microwave clads are developed on AISI 420 substrate with a microwave exposure of 07 min. The developed clad shown great improvement in the erosion resistance than substrate. Slurry erosive wear studies were carried out with focus of three important parameters such as speed, impact angle and time of slurry exposure. ANOVA and control factors analysis studies were carried out with 95% of confidence level. Impact angle shown most dominating parameter on wear rate. Mixed mode of erosion was noticed on the target surface.